The development of information literacy in early childhood education teachers: A study from the perspective of the education center's character - Juan Manuel Trujillo Torres; Gerardo Gómez García; Magdalena Ramos Navas-Parejo; Rebeca Soler Costa (OmniaScience, 2020)
The development of the digital competence is one of the current challenges of the educational community. Specifically, the area of information literacy is presented as a main pillar for the subsequent optimal development of a digital teaching competence. Based on this, the present article aims to evaluate the area of information literacy in practicing teachers from Early Childhood Education (N=57). A descriptive and inferential quantitative analysis was made for this piece of work in order to analyze the perceptions of the teachers towards this area, the accomplishment of the t-student test for the comparison of means between teachers of public and private with state-funded financial support centers and the application of a linear regression model that allows to predict the information literacy through the variable "education center". The results obtained reflected an optimal level of perceptions as for the information area, regardless of the type of school, as well as the possible prediction, regarding the school typology, of some information literacy variables.